Student Cognitive Presence in Small Group Collaboration Facilitated by Mobile Instant Messaging - QIAO, Yuhan; TANG, Ying; HEW, Khe Foon (International Journal of Educational Technology and Learning, 2018)
Cognitive presence describes the co-construction of knowledge in an online learning community. Few previous studies examined the development of cognitive presence in using mobile instant messaging (MIM) for academic purposes. Specifically, students nowadays set up small-size MIM discussion groups to work on group projects in higher education. No study has examined the establishment of cognitive presence in these small groups. This paper reports a multi-case study, investigating three self-initiated discussion groups in higher education. Data were collected primarily from the online interactive records and students’ semi-structured interviews. The Community of Inquiry framework was utilized as the guidance for coding process. The results show that students demonstrated cognitive presence in the group discussions, yet only 36% of the total messages contained indicators of cognitive presence. The majority (64%) of messages were on non-academic topics, such as greetings and casual social talks. In the interviews, we found students like using MIM for social purposes, but not for academic purposes, due to the social nature of MIM, the possible delayed responses, and the lack of “facilitators”.